Genome-Wide Gene Expression Changes in the Normal-Appearing Airway during the Evolution of Smoking-Associated Lung Adenocarcinoma - Kantrowitz, Jacob (Cancer Prev Res (Phila), 2018)
Smoking perpetuates in cytologically normal airways a molecular “field of injury” that is pertinent to lung cancer and early detection. The evolution of airway field changes prior to lung oncogenesis is poorly understood largely due to the long latency of lung cancer in smokers. Here, we studied airway expression changes prior to lung cancer onset in mice with knockout of the Gprc5a gene (Gprc5a(−/−)) and tobacco carcinogen (NNK) exposure and that develop the most common type of lung cancer, lung adenocarcinoma, within 6 months following exposure. Airway epithelial brushings were collected from Gprc5a(−/−) mice before exposure and at multiple times post-NNK until time of lung adenocarcinoma development and then analyzed by RNA sequencing. Temporal airway profiles were identified by linear models and analyzed by comparative genomics in normal airways of human smokers with and without lung cancer. We identified significantly altered profiles (n = 926) in the NNK-exposed mouse normal airways relative to baseline epithelia, a subset of which were concordantly modulated with smoking status in the human airway. Among airway profiles that were significantly modulated following NNK, we found that expression changes (n = 22) occurring as early as 2 months following exposure were significantly associated with lung cancer status when examined in airways of human smokers. Furthermore, a subset of a recently reported human bronchial gene classifier (Percepta; n = 56) was enriched in the temporal mouse airway profiles. We underscore evolutionarily conserved profiles in the normal-appearing airway that develop prior to lung oncogenesis and that comprise viable markers for early lung cancer detection in suspect smokers.